Biological control potential of plant growth‐promoting rhizobacteria suppression of Meloidogyne incognita on cotton and Heterodera glycines on soybean: A review - Xiang, Ni; Lawrence, Kathy S.; Donald, Patricia A. (Journal of phytopathology, 2018)
Over the past decade, we have seen an increasing market for biopesticides and an increase in number of microbial control studies directed towards plant‐parasitic nematodes. This literature survey provides an overview of research on biological control of two economically important plant‐parasitic nematodes, Meloidogyne incognita (Kofoid & White) Chitwood (southern root‐knot nematode) and Heterodera glycines Ichinohe (soybean cyst nematode) using spore‐forming plant growth‐promoting rhizobacteria (PGPR). In this review, the current biological control strategies for the management of those cotton and soybean nematodes, the mechanism of using BacillusPGPR for biological control of plant‐parasitic nematode including induced systemic resistance and antagonism and the future of biological control agents on management of plant‐parasitic nematodes are covered.